Empirical Testing of Corporate Governance, and ESG Risk Scores: Their Effect on Company Value - Alfredo, Harold Kevin; Pratama, Mohammad Irfan; Anita, Anita; Sejati, Hiro (Dinasti International Journal of Economics, Finance & Accounting, 2025)
There are still few previous studies in Indonesia that have conducted research using corporate governance, and Environmental, Social, and Governance risk scores as independent variables with company value as the dependent variable. So, this research aims to determine the influence of corporate governance and ESG scores on the value of companies included in Morningstar Sustainalytics. This research is a quantitative type of research using the size of the board of commissioners, independent commissioners, and gender diversity, as a proxy for corporate governance, the Morningstar Sustainalytics version of the ESG risk score as a proxy for the ESG rating. Company size and leverage are used as control variables in this study, and Tobin's Q as a proxy for company value. The research results found that corporate governance variables (board size, independent commissioners, and gender diversity) and ESG risk scores had a positive effect, however, they did not have a statistically significant effect on company value. This means that, statistically, the variables used are not able to convincingly explain changes in the company's market value as measured using Tobin's Q.